The PENGARUH METODE LEARNING BY DOING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI GERAK DAN GAYA PADA KURIKULUM MERDEKA - Akbar, Rizki; R. Ahmad Zaky El Islami; Annisa Novianti Taufik (UNIB Press, 2025)
This study aims to determine the effect of the learning by doing method on students' problem-solving abilities on the material of motion and force in the Merdeka curriculum. The learning-by-doing method was chosen because it emphasizes learning through direct experience, which is expected to increase students' active involvement and problem-solving skills. This study used a quasi-experimental design with the Pretest-Posttest Nonequivalent Control Group Design approach, involving two classes of junior high school students, namely the experimental class using the learning by doing method and the control class using the lecture method. The research instruments consisted of a problem-solving ability test in essay form, observation sheets, and student response questionnaires. The results showed that the learning by doing method had a significant effect on improving students' problem-solving abilities according to the independent sample t-test, producing a significance value of 0.01 (<0.05), which indicated that H0 was rejected and H1 was accepted.